Evaluation of Facial Soft-Tissue Morphology among Different Vertical Skeletal Profile - Ghadir Abdulal; Aly Osman; Ahmed Abyad (European Scientific Journal, ESJ, 2022)
The objective of this study was to compare facial groups classified according to their vertical skeletal characteristics (hypodivergent, normodivergent, and hyperdivergent) and to their respective soft tissue morphological features, particularly those relating to the lips and chin. 90 Lateral cephalometric x-rays were collected from the Orthodontic clinic at the Faculty of Dentistry, Beirut Arab University and divided into 3 equal groups based on mandibular plane angle, hypodivergent facial type (SN/MP <27°), normodivergent facial type (SN/MP between 27° and 37°), hyperdivergent facial type (SN/MP >37°). The mean upper and lower lips thickness was maximum among hypodivergent group (8.95 mm and 9.35 mm, respectively). The mean upper lip height was maximum among hyperdivergent group (11.3 mm), while lower lip height was maximum among hypodivergent group (25.32 mm). The mean procumbency of upper (PUL) and lower lips (PLL) was maximum among hypodivergent (2.08 mm and 0.87 mm, respectively). However, the mean chin thickness was maximum among hyperdivergent group (7.84 mm). Statistically significant difference among the three groups were observed only in Hypo vs Normo-divergent groups in ULT. Concerning PUL and PLL, there was a statistically significant differences between the different groups in Hypo vs Normodivergent and Hypo vs Hyperdivergent groups. It was concluded that the thickness of upper and lower lip, height of lower lip, and procumbency of both lips showed to be greater in hypodivergent facial patterns.